Suggestopedia in Arabic Language Learning (A Case Study of Reading Skills Instruction for Seventh-Grade Students at MTs N 4 Jember) - Siti Nurfadhilah; Sa’idatul Abidah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
There are four language skills, such as listening, reading, speaking, and writing. These skills are from the goal of universal Arabic education that must be learned, so that all students can master it. Reading skills require serious attention because reading skills cannot be obtained automatically, but must be studied and practiced. However, there are many aspects that cause difficulties for students in the learning process. One of the reasons is that there are various kinds of student personalities in the classroom that make teachers must be smart in choosing methods. One of the appropriate strategies as an effort to handle the case is to use the "suggestopedia method". To train students' reading skills, they need a suitable method, the existence of Arabic learning, using the suggestopedia method can focus students to practice reading Arabic text readings. There is in the classroom without the emergence of a sense of guilt and feelings of inadequacy. This study aims to describe the efforts to implement the suggestopedia method in learning to read maharah in Arabic. This research uses a qualitative approach, with a case study method, information is collected through observation and documentation. Information analysis in this study uses the theory of "Miles and Huberman". The results of the research show that the implementation of the suggestopedia method can improve reading skills in Arabic language education for seventh grade students of MTsN 4 Jember. The students experienced an increase in the activeness, confidence, and enthusiasm of the students, especially in reading skills. The improvement in question, namely the improvement of the process and student learning outcomes, which can be seen from the learning process of the first meeting and the second meeting. According to the results of the previous study, the researcher suggested the teachers to use the suggestopedia method as an alternative for teaching other materials.